Combustion and Emission Characteristics of a Diesel Engine Fueled with Crude Palm Oil Blends at Various Idling Speeds - Jun Cong Ge; Sam Ki Yoon; Jun Hee Song (Applied Sciences, 2022)
At present, the preparation cost of biodiesel is still higher than that of diesel. Thus, directly using vegetable oil before transesterification can greatly reduce the cost. This study investigated the application characteristics of the direct use of crude palm oil (CPO) in a common rail direct injection (CRDI) diesel engine. In this study, the combustion characteristics, engine performance, and emission characteristics of the CRDI diesel engine operated with CPO0 (neat diesel fuel), CPO10 (10% CPO blended with 90% diesel fuel by volume), CPO30 (30% CPO blended with 70% diesel fuel by volume), and CPO50 (50% CPO blended with 50% diesel fuel by volume) at three idling speeds (750 rpm, 1500 rpm, and 2250 rpm) were evaluated. The results obtained from the experiment elucidate that combustion starts earlier by increasing the idling speed. The addition of CPO to diesel fuel resulted in a decrease in the peak in-cylinder pressure at all idle speeds and a decrease in the maximum heat release rate (HRRmax) at 750 and 1500 rpm, but an increase in HRRmax at 2250 rpm. On the other hand, increasing idle speed is beneficial for reducing carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx), but it increases smoke emissions. In addition, adding 10% and 30% CPO to diesel fuel can reduce both HC, NOx, and smoke emissions simultaneously.